Medicaid reimbursement for community violence intervention and prevention (CVI): a multi-state policy implementation case study - Sheetal Ranjan; C. Clare Strange; Katheryne Pugliese (Health & Justice)
Abstract Background Violence has fluctuated in the United States in recent years. Additionally, policing practices have been challenged, especially in neighborhoods of color. Community Violence Intervention (CVI) programs have emerged as an effective policy to address violence through neighborhood-centered resources, trauma-informed care, and credible messengers, without full reliance on law enforcement officials. However, inconsistent funding challenges the feasibility and sustainability of these programs. In 2021 several states introduced policies to allocate Medicaid reimbursement for CVI services offering a promising solution to a more sustainable stream of funding. Methods This study uses rigorous qualitative analysis to evaluate the implementation of Medicaid reimbursement policies in California, Illinois, and Connecticut, applying the Exploration-Preparation-Implementation-Sustainment (EPIS) model. An analysis of secondary documentation and semi-structured interviews with key stakeholders from the first three states to implement the policy. Stakeholders were recruited from a variety of policy, medical, and non-profit sectors to provide their perspectives and expertise on implementation. Results Interviews with stakeholders from policy, medical, and non-profit sectors and a deep analysis of secondary documentation identifies key successes and barriers to effective implementation of Medicaid reimbursement policies across the United States. Acknowledging the barriers of implementation highlights where policy planning and development fails to be properly implemented on the ground. Findings emphasize the need for state-specific policy adaptation, collaboration amongst policymakers and practitioners, and sufficient training for on-the-ground CVI staff members. Conclusions Implementation of a Medicaid reimbursement policy for CVI programs could improve the efficacy and sustainability of such programs. However, states need to be aware of the challenges that may arise during the planning and implementation phases. The findings from this study reveal that policy makers, service providers and medical professionals need to be involved and collaborative throughout the planning and implementation process of the policy. States that are planning to implement these policies should assess whether they are ready to implement the policy to ensure that it is successful in the long term.